Aplikace metody dematel v integrovaném rámci správy společností - Klozíková, Jana; Dočkalíková, Iveta (Univerzita Pardubice, 2015)
Corporate governance was created in recent decades and we can say that it is a new field of science. The most famous companies failed from day to day. Their failure and scandals had significant impact on local and international community. Finding of a new effective framework of level of corporate governance can help that the similar negative events wouldn't be repeated never again. The new approach in the corporate governance - an integrated framework, created for corporate governance is one of the ways to improve this area. This article responds to this reality presenting the fact, that not only the approach mentioned above, but it also eliminates shortages of this approach, which were criticized for integrated framework of corporate governance. The present period offers a variety of methods leading to accuracy and improvement of current approaches, but an area of corporate governance is mainly established on qualitative criteria, rather than on quantitative criteria. Corporate governance is a new field of science. Due to this fact it offers the question of the utilization of new techniques and knowledge that lead to the improvement of the level of corporate governance. The method of multi-criteria decision-making method DEMATEL allows removal of the weaknesses of an integrated framework of corporate governance, which can be taken into account in the context of a causal connection, which exists between the different tools of integrated framework.
Application of dematel method in integrated framework of corporate governance
Keywords: corporate governance; MADM – multiple attribute decision making methods; integrated framework; DEMATEL; decision making; C02; G30; G34